The Problems of the RF Labor Law Code Implementation and State Federal Supervision Enforcement in the Sphere of Labor Relations - Kanunnikov A. B.; Pastukhov A. A. (Vestnik Omskoj Ûridičeskoj Akademii, 2014)
The article deals with the problems of the RF Labor Law Code implementation. The authors study the theoretical and practical aspects of the state federal supervision enforcement in the sphere of labor legislation